Al-Qaeda’s New Orientation After the Death of Osama bin Laden - Siti Fatimah; Yanuardi Syukur (Jurnal Studi Sosial dan Politik, 2019)
After the death of Osama Bin Laden and the declaration of the establishment of the Islamic State in Iraq and Syria (ISIS), the Al-Qaeda movement changed from being aggressive to being passive. The aggressiveness of the Al-Qaeda movement, for instance, was seen during the spectacular terror of 9/11, which was then followed by various actions carried out by followers in various parts of the world. However, Bin Laden's death and the rise of the ISIS group made Al-Qaeda look passive. This paper seeks to see the history of the Al-Qaeda movement to the dynamics that influence the movement’s choices. The author found that changing Al-Qaeda's orientation from aggressive to passive did not deny the existence of a consolidated movement that deliberately distanced itself from the anti-terrorism campaign carried out by the United States.